[RETRACTED] Model Pendidikan Karakter Berbasis Kearifan Lokal - Mutaqin, Enjen Zaenal; Hayati, Fitroh; Aulia, Elsa Sivia Nur (LPPM UIN Saizu Purwokerto, 2024)
This article is retracted because it has been published in another publication (Proceedings of the 3rd Asian Education Symposium (AES 2018)) in English version with the title